2022
DOI: 10.1177/27526461211066496
|View full text |Cite
|
Sign up to set email alerts
|

Collisions of difference: Teaching gender and sexuality in a conservative and religious culture

Abstract: Gender and sexuality have been at the forefront of societal debate in recent years with various legal battles concerning LGBT rights and religious liberties taking center stage. Shifts in attitudes and gains in legal protections have served to entrench conservative religious beliefs and to perpetuate generational “bitter” knowledge. This study seeks to understand the types of beliefs brought into the classroom by students and to examine the role of religious socialization in shaping and maintaining problematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Social beliefs, stereotype judgments, and dominant cultural norms can lead to a deficiency of knowledge about sexuality, and this may narrow down the perspectives of individuals about different sexual orientations. It can also limit individuals in terms of receiving information about sexuality (Ingersoll & Cook, 2022; Lynch & Joosten, 2022). In studies conducted with the participation of university students, it has been reported that the geographical region where the individual was raised can be effective on sexual myths (Evcili & Golbasi, 2017; Örüklü et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Social beliefs, stereotype judgments, and dominant cultural norms can lead to a deficiency of knowledge about sexuality, and this may narrow down the perspectives of individuals about different sexual orientations. It can also limit individuals in terms of receiving information about sexuality (Ingersoll & Cook, 2022; Lynch & Joosten, 2022). In studies conducted with the participation of university students, it has been reported that the geographical region where the individual was raised can be effective on sexual myths (Evcili & Golbasi, 2017; Örüklü et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente conviene abordar tres ideas fundamentales ahondadas ya por autores como Ingersoll & Cook (2022), Miller (2022) y Miller et al (2022, el tema de las identidades y el género continúa siendo una reflexión permanente al interior de las instituciones educativas; un punto de inflexión y conexión a la vez sustenta la idea de la equidad en la educación desde donde los estudiantes se implican y aúnan esfuerzos para encontrarse con sus pares y el liderazgo en la escuela con sus estudiantes posibilitan aprendizajes significativos que surgen como posibilitadores de una educación siempre vinculante.…”
Section: Los Aparentesunclassified